Neurokinin B and Neurokinin-3 Receptor Signaling: Promising Developments in the Management of Menopausal Hot Flushes - Modi, Manish; Dhillo, Waljit S. (Seminars in Reproductive Medicine, 2019)
Vasomotor symptoms, including hot flushes and night sweats, pose a significant symptomatic burden to women undergoing menopause, and negatively impact on both their physical and psychological well-being. Management of these symptoms can be challenging, with the use of conventional hormone replacement therapy limited by duration of treatment and clinical contraindications. Recent advances in our understanding of the neuroendocrine regulation of the reproductive axis and thermoregulation postmenopause has helped identify a promising new therapeutic target to ameliorate hot flushes. Antagonism of the neurokinin B/neurokinin-3 receptor (NK3R) signaling pathway has emerged as an efficacious treatment in managing vasomotor symptoms, with evidence of rapid and sustained reduction in hot flush frequency and severity and improvements in secondary quality-of-life measures such as sleep. Within this review, we will explore the growing body of evidence supporting the use of NK3R antagonists in the management of vasomotor symptoms, and the possible utility in managing dysfunctional sex-hormone–dependent disorders and glycolipid metabolism disorders such as polycystic ovarian syndrome.
Keywords: hot flushes; neurokinin B; neurokinin 3 receptor; menopause